1996
DOI: 10.1080/00397919608004575
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of 1H-Pyrazole-5-propanoic and 1H-Pyrazole-5-butanoic Acids from Dilithiated C(α),N-Carboalkoxyhydrazones and Succinic or Glutaric Acid Anhydrides

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Pyrazoles are widely studied five-membered heterocyclic compounds. Pyrazole derivatives exhibit antitumor, antiinflammatory, analgesic, antipyretic, 1 antimicrobial, 10 antiocoagulant, 11 and agrochemical 12 activity. Pyrazoloquinoline derivatives, which interact with the central benzodiazepine receptors are important tools for finding out the physiological properties and the structural requirements of the recognition site of the receptor itself.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoles are widely studied five-membered heterocyclic compounds. Pyrazole derivatives exhibit antitumor, antiinflammatory, analgesic, antipyretic, 1 antimicrobial, 10 antiocoagulant, 11 and agrochemical 12 activity. Pyrazoloquinoline derivatives, which interact with the central benzodiazepine receptors are important tools for finding out the physiological properties and the structural requirements of the recognition site of the receptor itself.…”
Section: Introductionmentioning
confidence: 99%
“…We have been involved with the preparation and condensation of dilithiated C (α), N -carboalkoxyhydrazones, where hydrazones were polylithiated with excess lithium diisopropylamide (LDA), followed by condensation with a variety of esters for the preparation of substituted pyrazoles or pyrazole-related products. Polyanion-type preparations of others 11 have used similar entry compounds, related electrophilic reagents, and different experimental conditions ( n -butyllithium, −78 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Convenient subjects for solving this problem are the 3-(4-formyl-1-pyrazolyl)propionic acids, described in [1], the aldehyde group of which may readily be converted sequentially into vinyl-and ethylcarboxyl functions. Derivatives of 3-pyrazolylacrylic and 3-pyrazolylpropionic acids attract the steady attention of investigators since substances with high pharmacological activity are found among them [3][4][5].…”
mentioning
confidence: 99%
“…Convenient subjects for solving this problem are the 3-(4-formyl-1-pyrazolyl)propionic acids, described in [1], the aldehyde group of which may readily be converted sequentially into vinyl-and ethylcarboxyl functions. Derivatives of 3-pyrazolylacrylic and 3-pyrazolylpropionic acids attract the steady attention of investigators since substances with high pharmacological activity are found among them [3][4][5].For this reason we carried out the Knoevenagel reaction of 3-(3-aryl-4-formyl-1-pyrazolyl)propionic acids 1a-i with malonic acid under microwave activation conditions, which for some time past has been widely applied in the synthesis and conversions of heterocyclic compounds [6]. However, the microwave variant of the Knoevenagel reaction is limited by the use of chalcones and cinnamic acids in the synthesis [7].…”
mentioning
confidence: 99%